Bioactivity of Circulatory Factors After Pulmonary Exposure to Mild or Stainless Steel Welding Fumes. (8th June 2020) - Kodali, Vamsi; Shoeb, Mohammad; Meighan, Terence G; Eye, Tracy; Friend, Sherri A; Hubczak, John; Kashon, Michael L; Zeidler-Erdely, Patti C; Antonini, James M; Erdely, Aaron
Abstract: Studies suggest that alterations in circulating factors are a driver of pulmonary-induced cardiovascular dysfunction. To evaluate, if circulating factors effect endothelial function after a pulmonary exposure to welding fumes, an exposure known to induce cardiovascular dysfunction, serum collected from Sprague Dawley rats 24 h after an intratracheal instillation exposure to 2 mg/rat of 2 compositionally distinct metal-rich welding fume particulates (manual metal arc welding using stainless steel electrodes [MMA-SS] or gas metal arc welding using mild steel electrodes [GMA-MS]) or saline was used to test molecular and functional effects of in vitro cultures of primary cardiac microvascular endothelial cells (PCMEs) or ex vivo organ cultures. The welding fumes elicited significant pulmonary injury and inflammation with only minor changes in measured serum antioxidant and cytokine levels. PCME cells were challenged for 4 h with serum collected from exposed rats, and 84 genes related to endothelial function were analyzed. Changes in relative mRNA patterns indicated that serum from rats exposed to MMA-SS, and not GMA-MS or PBS, could influence several functional aspects related to endothelial cells, including cell migration, angiogenesis, inflammation, and vascular function. The predictions were confirmed using a functional in vitro assay (scratch assay) as well as an ex vivo multicellular environment (aortic ring angiogenesis assay), validating the concept that endothelial cells can be used as an effective screening tool of exposed workers for determining bioactivity of altered circulatory factors. Overall, the results indicate that pulmonary MMA-SS fume exposure can cause altered endothelial function systemically via altered circulating factors.